Caracterização das viagens geradas por um pgv comercial: estudo de caso no Supermercado Queiroz em Caraúbas/RN - Oliveira, Érico Nirondy Tôrres (Universidade Federal Rural do Semi-Árido, 2018)
With the growth of the urbanization process in all regions of Brazil, there is a considerable increase in the number of commercial enterprises and, consequently, the volume of traffic around them. According to ITE (1992) it considers PGV as centers of activities with high density of development, that attract a great concentration of traffic of vehicles and / or pedestrians. The research aims to characterize the trips of the users to the PGV under study, to identify the main attraction of this movement to the Supermarket Queiroz and to understand the reasons that lead the population to make this choice, since there are other establishments of this type in the city of Caraúbas. The study is composed of two phases: In the first phase, the data are collected through the application of the questionnaire to the sampled group and the second phase is linked to an analysis of the data collected in the first phase. According to analysis of the results, Queiroz Supermarket in the city of Caraúbas-RN, is classified as commercial and large, it was noted that the trips are characterized as primaries, attracted by the price, with the purpose of purchases, the largest part of the users are female and income range 0 to 5 minimum wages, mostly moving the motorcycle mode.
Monografia
Keywords: PGV; Viagem; Atração; ENGENHARIAS::ENGENHARIA CIVIL